GAYA BAHASA PENEGASAN USTAZ MUHAMMAD NUR MAULANA DALAM ACARA ISLAM ITU INDAH - Devi Ratna Julyarti; Charlina '; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the assertion language style used by cleric Maulana Nur Muhammad in Islam itu Indah event. This study discusses the language style affirmation used by Ustaz Muhammad Nur Maulana in the event of Islam itu Indah and the results of this study found a style affirmation used by Ustaz Muhammad Nur Maulana is stylistic repetition, tautology, climax, anti- climax, ellipsis, koreksio, asidenton, polisidenton, eksklamasio and preterisio this study used a qualitative approach with descriptive analysis method which aims to analyze and explain in descriptive results obtained in the study. Results of the research is the analysis of language style affirmation cleric Maulana Nur Muhammad in Islam itu Indah event .Keywords: The assertion language style, Ustadz Muhammad Nur Maulana, in Islam itu Indah event.